One Health approach at the heart of the French Committee for monitoring and anticipating health risks - Thierry Lefrançois; Bruno Lina; COVARS; Brigitte Autran (Nature Communications, 2023)
The French Committee for Monitoring and Anticipating Health Risks (COVARS) has been strengthening the One Health approach through its interdisciplinary and multi-sectoral composition, the emerging risks it addresses (Covid-19, Mpox, vector-borne diseases, avian influenza…), its holistic approach to risks and its position at the science-decision interface.